Prospects and Constraints of Commercial Cutflower Production in Thiruvananthapuram District - Sindhu S (Department of Agricultural Extension, College of Agriculture, 1997)
The present study under the title "Prospects and constraints of cutflower production in Thiruvananthapuram district" was undertaken with the following objectives. 1. To delineate the components of conceptual skill and to measure the conceptual skill of growers. 2. To study the relationship of personal, socio-situational and economic factors with the conceptual skill of growers. 3. To study the production practices of cutflowers followed by the growers. 4. To identify the different marketing channels existing in cutflower marketing in consultation with the growers. 5. To identify the constraints related to cutflower production and marketing as perceived by growers. The study was conducted among the respondents of five cutflower societies functioning in Thiruvananthapuram district. A sample of 100 growers were selected from the societies by adopting stratified random sampling technique with proportionate sampling procedure. Data was collected with the help of well structured, pre tested interview schedule and suitable statistical tests were employed in the analysis of data. In the study conceptual skill has been considered as dependent variable. The factors such as planning, risk-orientation, decision-taking ability, supervision and market perception were the major dimensions of conceptual skill. The selected personal, socio-situational and economic factors of cutflower growers were taken as independent variables which included education, cutflower growing experience, attitude towards cutflower growing, knowledge on cut flowers, self confidence, orientation towards competition, orientation towards skill development in farm workers, information seeking behaviour (personal), operational area, infra structural facilities, extension